Screening of Cotton Genotypes for Heat Tolerance - R, Asha; Ahamed M, Lal (International Journal of Bio-resource and Stress Management, 2023)
Cotton (Gossypium hirsutum L.) is being grown in both the tropical and temperate regions of the world and is greatly influenced by climatic factors. Cotton requires more than 180 days with temperature above 15oC and excessive temperature (above 36oC) affects its growth, development and reproduction significantly. The present investigation was carried out with 40 genotypes of cotton, collected from different parts of the country, at Agricultural College Farm, Bapatla to elicit information on heat tolerance using cellular membrane thermostability and enzyme viability. The mean relative electrical conductivity values showed gradual increase from 32.06 at 25oC to 84.15 at 50oC indicating higher temperatures had direct effect on the leakage of fluids from the cells and higher levels of cell injury. The dehydrogenase enzyme viability was reduced with the increase in the temperature from 30oC and 50oC. The genotypes L788, RAH 912 and Pee Dee 0113 showed high levels of heat tolerance in both the experiments at 500C and these genotypes can be exploited in the breeding programmes for heat tolerance. Genotypic differences for cellular membrane thermostability and enzyme viability were observed. The genotypic and phenotypic coefficients of variation were moderate while heritability coupled with high genetic advance as percentage of mean was high for these characters indicating the operation of additive gene action in controlling these traits. This study also indicated the importance of these parameters as easy screening tools for heat tolerance in cotton.